2007
DOI: 10.1053/j.ajkd.2006.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cystatin C With Poor Exercise Capacity and Heart Rate Recovery: Data From the Heart and Soul Study

Abstract: Background-Cystatin C, an alternative serum measure of kidney function, is a stronger predictor of cardiovascular events than creatinine or estimated glomerular filtration rate (eGFR). We hypothesized that serum cystatin C concentration would have a stronger more linear association with cardiovascular functional status than creatinine-based measures in outpatients with established coronary heart disease (CHD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Either of these mechanisms in isolation, or in concert, may account for these associations. Second, we have previously demonstrated that kidney dysfunction is associated with lower heart rate recovery after exercise testing, and heart rate recovery is an established marker of cardiovascular autonomic function 15. Since autonomic signaling in the left atrium and pulmonary veins is thought to be a key factor in the initiation and maintenance of AF, kidney dysfunction may lead to AF through its association with altered autonomic tone 16.…”
Section: Discussionmentioning
confidence: 99%
“…Either of these mechanisms in isolation, or in concert, may account for these associations. Second, we have previously demonstrated that kidney dysfunction is associated with lower heart rate recovery after exercise testing, and heart rate recovery is an established marker of cardiovascular autonomic function 15. Since autonomic signaling in the left atrium and pulmonary veins is thought to be a key factor in the initiation and maintenance of AF, kidney dysfunction may lead to AF through its association with altered autonomic tone 16.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the proportion of participants with poor exercise capacity was 45% among those with cystatin C concentration in the highest quartile (>1.3 mg/L) compared with 12% among those in the lowest quartile (<0.92mg/L, adjusted OR 3.2; 95%CI 1.6 to 6.5, p=0.001). 13 Leikis and colleagues also demonstrated 14 that as renal function declined over 2 years, there was a corresponding decrease in exercise performance even when hemoglobin was maintained.…”
Section: Physical Functioning and Frailty In Ckdmentioning
confidence: 98%
“…These relationships between cardiovascular disease and increased CysC concentrations have been described both in cohorts or sub-groups of patients selected on the basis of a past history of cardiovascular disease (216,217,219,221,225,226) and in patients without cardiovascular history (220, 222-224, 228, 229). Some also consider that increased CysC values may be associated with morphological cardiac abnormalities, such as left ventricular hypertrophy or left ventricular dysfunction on echocardiography (228), functional abnormalities, such as heart failure (230), or poor exercise tolerance (231). In all of these studies, the association between cardiovascular disease and CysC appeared to be stronger than with creatinine or GFR estimation algorithms based on creatinine.…”
Section: Future Perspectives For Cysc Applications Cysc As a Cardiovamentioning
confidence: 99%